2016
DOI: 10.1016/j.taap.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The trypanocidal benznidazole promotes adaptive response to oxidative injury: Involvement of the nuclear factor-erythroid 2-related factor-2 (Nrf2) and multidrug resistance associated protein 2 (MRP2)

Abstract: Oxidative stress is a frequent cause underlying drug-induced hepatotoxicity. Benznidazole (BZL) is the only antitripanocide agent available for treatment of Chagas disease in endemic areas. Its use is associated with side effects, including increases in biomarkers of hepatotoxicity. However, BZL potential to cause oxidative stress has been poorly investigated. Here, we evaluated the effect of a pharmacologically relevant BZL concentration (200 μM) at different time points on redox status and the counteracting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Among these genes, we identified CAT (catalase), GCLC (glutamate-cysteine ligase catalytic subunit), GCLM (glutamate-cysteine ligase modifier subunit), GPX1 (glutathione peroxidase 1), GSR (glutathione reductase), GSS (glutathione synthetase) and GSTP1 (glutathione S-transferase π1) (Additional file 2: Table S2). In contrast to our findings of downregulation of these genes, recent studies have shown enzymatic upregulation of CAT, SOD and GPX as a natural response to attenuate damage mediated by ROS/RNS after 12 h of exposure to BZ [28, 30]. These differences suggest that to evaluate the significance of these results, a strategy combining different time points could elucidate the true involvement of these molecules in host cell responses to BZ treatment.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Among these genes, we identified CAT (catalase), GCLC (glutamate-cysteine ligase catalytic subunit), GCLM (glutamate-cysteine ligase modifier subunit), GPX1 (glutathione peroxidase 1), GSR (glutathione reductase), GSS (glutathione synthetase) and GSTP1 (glutathione S-transferase π1) (Additional file 2: Table S2). In contrast to our findings of downregulation of these genes, recent studies have shown enzymatic upregulation of CAT, SOD and GPX as a natural response to attenuate damage mediated by ROS/RNS after 12 h of exposure to BZ [28, 30]. These differences suggest that to evaluate the significance of these results, a strategy combining different time points could elucidate the true involvement of these molecules in host cell responses to BZ treatment.…”
Section: Resultscontrasting
confidence: 99%
“…Despite the high mRNA expression levels of MRP2 observed in all treated conditions, the results suggest that this transporter may play a role in BZ detoxification. MRP2 has been reported to be involved in xenobiotic efflux, which potentially induces oxidative stress in host cells [28]. Moreover, MRP2 extrudes GSSG, which, along with de novo GSH synthesis, contributes to the return of normal GSH levels and redox homeostasis [28].…”
Section: Resultsmentioning
confidence: 99%
“…Although the full mechanism of action of benznidazole remains to be elucidated, these results indicate that ROS are not involved in benznidazole’s trypanocidal effects. Benznidazole also activates nuclear erythroid factor-2 (Nrf2) and protects the host from oxidative damage in a delayed time frame [ 16 ].…”
Section: Shifting the Old Paradigmmentioning
confidence: 99%
“…Activation of the Nrf2 pathway is a promising strategy for chemoprevention, however, some investigation has revealed that Nrf2 and its downstream detoxifying enzymes are overexpressed in various cancer cell lines and human cancer tissues, giving cancer cells an advantage for survival and growth [ 45 , 46 ]. In addition, Nrf2 is upregulated in multiple drug resistant (MDR) cancer cells, which accounts for the acquired chemoresistance [ 47 , 48 ]. The E2 induced MCF 10A cell model indicated that ATR-II had chemopreventive effects on MCF 10A cells associated with activating the Nrf2-ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 99%